Antimicrobial Drug Resistance Trends of Bacteria Causing Bloodstream Infections in a Diagnostic Centre in Lahore: Antimicrobial Drug Resistance Trends of Bacteria - Minahil, Sara; Nazeer, Kiran; Bashir, Muhammad Faisal `; Asif, Amina; Riaz, Saba (Pakistan BioMedical Journal, 2023)
Bacteraemia due to multidrug-resistant (MDR) bacteria, particularly those producing carbapenemase or extended-spectrum beta-lactamase (ESBL), causes a significant threat to patients and associated morbidity and mortality. The global rise in the incidence of bacteremia necessitates the rapid and accurate identification of pathogens to ensure effective patient health management. Objective: To investigate antimicrobial drug resistance trends among bacteria causing bloodstream infections from a diagnostic centre in Lahore. Methods: This research was conducted at the Institute of Microbiology and Molecular Genetics, University of the Punjab, Lahore and Citilab and Research Centre, Lahore, from January 2020 to December 2022. A total of 2919 blood samples were cultured to screen the bacteremia patients. Following standard protocols, four hundred twenty isolates proceeded for gram-staining, biochemical characterization, and antimicrobial susceptibility testing (AST). The AST results of each strain calculated multiple antibiotic resistance (MAR). Results: Of 420 bacterial isolates, Gram-negative and Gram-positive isolates accounted for 48.57% and 51.43%, respectively. The predominant pathogens were Staphylococcus epidermidis (48.10%) and Salmonella typhi (27.14%), with other significant pathogens including Klebsiella spp., Pseudomonas spp., Enterobacter, Acinetobacter spp., Escherichia coli, Staphylococcus aureus, Enterococcus spp., Citrobacter, Morganella morganii, and Proteus mirabilis. AST revealed high resistance to Cephalosporins, Nitrofurantoin, Fosfomycin, and Quinolones. In contrast, Carbapenems demonstrated notable sensitivity. Salmonella typhi and Staphylococcus epidermidis exhibit the highest MAR values. Conclusions: The study highlights the prevalence of multidrug resistance bacteremia-causing pathogens, with a concerning trend towards decreasing antibiotic efficacy.